Propoxyphene Mediates Oxyhemoglobin-Induced Injury in Rat Cortical Neurons Through Up-Regulation of Active-β-Catenin - Yuqian Li; Jiancai Wang; Zhihong Li; Hongyu Cheng; Zhuo Zhang; Tao Luo; Xingye Zhang; Guodong Gao; Huashan Lu; Lihong Li (Frontiers Media S.A., 2020)
Wnt/β-catenin signaling is involved in various biological processes, including the development of the central nervous system. The dysfunction of mitochondria has been shown to participate in the progress of subarachnoid hemorrhage (SAH). Traumatic subarachnoid hemorrhage (tSAH) is a serious complication in acute craniocerebral trauma. Opioids can activate the canonical Wnt/β-catenin signaling pathway. c-Myc, a downstream protein of Wnt/β-catenin signaling, contributes to the fusion of mitochondria. Here, we investigated the protective roles of Propoxyphene (Pro) against Oxyhemoglobin (OxyHb)-induced primary cultured neuron apoptosis. The data indicated that Pro rescued active-β-catenin from OxyHb-induced decline. Furthermore, Pro attenuated OxyHb-induced apoptosis and fission of mitochondria in primary cortical neurons. However, the protective effects were abrogated under active-β-catenin-deficient conditions. Together, the data presented here showed that Pro, a weak opioid analgesic drug, attenuates OxyHb-induced mitochondria-dependent apoptosis in an active-β-catenin-c-Myc-dependent manner.